Physicochemical characterisation of emulsified agarwood oil using gel electrophoresis - Boon, Yih Tien (2017)
Quality of the agarwood oil is very subjective and the market price of the oil mainly depends on the quality itself. GC-MS is one of the expensive analytical techniques that is used to determine the quality of the agarwood oil based on the major chemical compound detected. There is no simple and cheaper method established to determine the quality of the agarwood oil based on their physicochemical and electrical properties. Therefore, this dissertation describes three interdependent studies from the beginning in which sample preparation till sample quality were characterised using gel electrophoresis. The first study examined the role of non-ionic surfactant and its critical aggregation concentration (CAC) (0.0167% v/v) on the emulsification process of agarwood oil. The physicochemical properties of emulsified agarwood oil were studied with focus on their droplet size, surface charge, and chemical constituents. Each emulsified droplet consisted of a specific zeta potential value that represented its specific bioactive compounds that were trapped inside the droplets and responded to a specific molecular mass and electrophoretic mobility. Thus, gel electrophoresis technique was performed in the second study to separate the emulsion produced. Due to the nano size (80–100 nm) of emulsified droplet produced at CAC condition, SDSpolyacrylamide gel electrophoresis technique, which is an in-situ, reliable, and sustainable technique, was successfully performed to separate the emulsified oils based on their mobility through the gel in terms of molecular size. The third study used the mechanism and technique studied previously to determine the quality of two inoculated oil emulsions. GC-MS result reported that the high concentration of major compounds present in naturally inoculated agarwood oil led to a large molecular weight. To obtain a vivid visible band in the gel electrophoresis, the optimisation of the gel formulation was conducted to control the necessary pore size with the optimised formulation at 21% resolving gel with 48% acrylamide concentration and 3.33% cross-linker. Electrophoretic mobility of droplet through gel matrix was the main factor in evaluating the quality of emulsified oils in terms of their molecular weight. The high quality oil with large molecular weight (211 Da) migrated slower than the low quality oil with small molecular weight (195 Da) when both samples were subjected to gel electrophoresis.